KONSEKUENSI DOMINASI KEPEMILIKAN ASING VS DOMESTIK DAN KEBIJAKAN KEPEMILIKAN TUNGGAL PADA INDUSTRI PERBANKAN (Fokus Ekonomi, 2011)
This paper is concerned with two issues. First, This paper explained the consequencies of foreign ownership vs domestic ownership on banking Industry. Second, there is single presence policy. This study of literature can be simplified that foreign ownership, domestic ownership and single presence policy can effect negative or positive on risk taking or moral hazard depend on charter value. The single presence policy improve an ownership concentration. Ownership concrentation effect on risk taking.  When the charter value is low, domestic ownership, foreign ownership dan ownership concentration are more  risk taking.. This mean that charter value is incentive to take risk.  The perspective has support to moral hazard or entrenchment agency theory, but not for high charter value. When the charter value is low, they are low risk taking.